TEKNITECHNIQUES FOR CULTIVATION OF CATFISH (Clarias. Sp.) AQUAPONIC SYSTEM BUDIKDAMBER TO IMPROVE STUDENT'S CREATIVITY AT SMKK BUDIDAYA IKAN LELE (Clarias. Sp.) SISTEM AKUAPONIK BUDIKDAMBER UNTUK MENINGKATKAN KREATIVITAS SISWA DI SMK NEGERI 6 LHOKSEUMAWE - Salamah; Rachmawati Rusydi; Mahdaliana (LPPM dan PM Universitas Samudra, 2022)
The purpose of this activity is to provide an overview of information regarding the cultivation of catfish in the aquaponic system of Budikdamber (bucket cultivation) to increase student creativity and open up business opportunities for students. This training activity is an illustration of how a bucket (budikdamber) can be used to increase student income and open up knowledge for students. Students can carry out cultivation activities with narrow land and lower costs, besides that this aquaponics system is also effective and efficient to be applied in schools. The cultivation method of catfish with the Budikdamber aquaponic system uses probiotics to maintain water quality during maintenance. The frequency of feeding is twice a day, namely in the morning and evening, the amount of feed given is based on the body weight of the fish. After participating in this activity, students can understand and carry out catfish cultivation with the aquaponic system of budikdamber (cultivating in buckets. The result of this service activity is the development of student insight about catfish farming in buckets (budikdamber) with an aquaponic system and also students' skills in processing and caring for catfish and cultivated plants.Furthermore, the development of catfish enlargement cultivation can optimize the use of available land to increase production yields. Keywords: Aquaponics, catfish, budikdamber system